Experience with the technique of subperiosteal suspension urethrovesical angle for vaginal surgical repair of urinary incontinence. - Pacheco Romero, José (2015)
The author's experience with surgical repair of urinary incontinence (SUI) using the technique of subperiosteal suspension in two successive groups of 40 and 33 patients with a minimum follow-up of 2 years, respectively, is presented. Age was similar in both groups and there were fewer large multiparous in the second group. SUI was more severe and moderate degree of genital prolapse was also moderate or moderate to severe. In the surgical repair one thick silk suture used is preferably 0, performing the approximation of the levator ani. Foley catheter was removed on the third day. As in the first series, the result was positive in 90 percent in the second group, so far no patient reported recurrence of SUI, giving a favorable outcome of 95 percent in 73 patients. Cystocele recurred in 25 percent in the first group and 12 percent in the second group, always mild. These results are comparable to the best reported recently, which appreciates the value of the vagina in the repair of SUI in selected cases, with proper technique and skilled hands.